PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Annisa Resty Amalia, 12.05.52.0087; Nurhayati, Ida (Students Journal of Accounting and Banking, 2017)
This study aims to determine the effect of the current ratio, quick ratio, debt to equity ratio, debt to total assets, total asset turnover and inventory turnover to changes in earnings in manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2013-2015. The population used in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) during the years 2013-2015. The sampling technique in this research is purposive sampling. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing can be concluded that the current ratio does not affect the profit change. Quick ratio change has no effect on earnings. Debt To Equity Ratio does not affect the profit change. Total Debt to Total Assets negative effect on profit change. Total Assets Turnover positive affect the profit change. Inventory turnover did not affect the profit change.Keywords: current ratio, quick ratio, debt to equity ratio, debt to total assets, total asset turnover, inventory turnover and profit changes